PENINGKATAN LITERASI ALKITABIAH MELALUI PROGRAM GEMAR BACA ALKITAB DI GEREJA REFORMASI INDONESIA NGABANG - Wiyono, Slamet; Netsen; Hanock, Edward E.; Laoli, Arosokhi (Jurnal PKM Setiadharma, 2024)
The "Gemar Baca Alkitab" program at Gereja Reformasi Indonesia Plasma V Ngabang aims to enhance biblical literacy among children through interactive, creative, and contextual approaches. The program involves collaboration between church leadership and theology students from STT Makedonia, who act as facilitators. By utilizing multisensory methods such as Bible reading, interactive discussions, and creative activities, the program strives to strengthen the children’s understanding of biblical teachings, while helping them apply Christian values in their daily lives. This initiative addresses the challenge of declining interest in biblical learning due to the pervasive influence of digital technology. It successfully engages children by integrating elements of technology and fostering an environment of active participation. The results show significant improvements in biblical literacy, moral character development, and children’s motivation to engage with biblical texts. The program's success offers potential for replication in other church communities.